Clinical efficacy and mechanism of probiotics in allergic diseases - Ha-Jung Kim; Hyung Young Kim; So-Yeon Lee; Ju-Hee Seo; Eun Lee; Soo-Jong Hong (Korean Pediatric Society, 2013)
A complex interplay between genetic and environmental factors partially contributes to the development of allergic diseases by affecting development during prenatal and early life. To explain the dramatic increase in the prevalence of allergic diseases, the hygiene hypothesis proposed that early exposure to infection prevented allergic diseases. The hygiene hypothesis has changed to the microbial hypothesis, in which exposure to microbes is closely linked to the development of the early immune system and allergic diseases. The intestinal flora may contribute to allergic disease through its substantial effect on mucosal immunity. Based on findings that exposure to microbial flora early in life can change the Th1/Th2 balance, thus favoring a Th1 cell response, probiotics may be beneficial in preventing allergic diseases. However, evidence from clinical and basic research to prove the efficacy of probiotics in preventing allergy is lacking. To date, studies have yielded inconsistent findings on the usefulness of probiotics in allergic diseases. It is difficult to demonstrate an exact effect of probiotics on asthma, allergic rhinitis, and food allergy because of study limitations, such as different first supplementation period, duration, different strains, short follow-up period, and host factors. However, many studies have demonstrated a significant clinical improvement in atopic dermatitis with the use of probiotics. An accurate understanding of the development of human immunity, intestinal barrier function, intestinal microbiota, and systemic immunity is required to comprehend the effects of probiotics on allergic diseases.